1996
DOI: 10.1182/blood.v87.6.2435.bloodjournal8762435
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus (EBV)-associated lymphoproliferations in severe combined immunodeficient mice transplanted with Hodgkin's disease lymph nodes: implications of EBV-positive bystander B lymphocytes rather than EBV-infected Reed-Sternberg cells

Abstract: To establish an in vivo model for the study of Hodgkin's disease and Reed-Sternberg (RS) cells, 25 lymph node tissue samples involved by Hodgkin's disease were grafted into severe combined immunodeficiency (SCID) mice. Ten Epstein-Barr virus (EBV)-associated tumors were obtained in SCID mice. EBV-positive tumors growing in SCID mice were correlated with the presence of EBV-positive nonneoplastic B cells in patient tumors (90% v 26.6%; P>.01) and was independent of the EBV status of RS cells. Our results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
5
5
0
Order By: Relevance
“…Tumors were obtained from each biopsy and then established in vitro, providing cell lines L1, L2, L3, and L4, corresponding to patients P1, P2, P3, and P4, respectively. As previously reported (13), the L1, L2, L3, and L4 cell lines exhibited a phenotype of activated B lymphocytes with expression of CD19, CD20, CD21, CD22, CD23, and CD30 antigens, while T-cell antigens (CD3, CD4, and CD8) were not detected (data not shown). In addition, LMP-1 and EBV nuclear antigen 2 were also expressed in these lymphoblastoid cell lines known to originate from EBV-positive reservoir lymphocytes present in the original lymph nodes (13,15).…”
Section: Epstein-barr Virus (Ebv) Is Now Firmly Associated Withsupporting
confidence: 87%
See 3 more Smart Citations
“…Tumors were obtained from each biopsy and then established in vitro, providing cell lines L1, L2, L3, and L4, corresponding to patients P1, P2, P3, and P4, respectively. As previously reported (13), the L1, L2, L3, and L4 cell lines exhibited a phenotype of activated B lymphocytes with expression of CD19, CD20, CD21, CD22, CD23, and CD30 antigens, while T-cell antigens (CD3, CD4, and CD8) were not detected (data not shown). In addition, LMP-1 and EBV nuclear antigen 2 were also expressed in these lymphoblastoid cell lines known to originate from EBV-positive reservoir lymphocytes present in the original lymph nodes (13,15).…”
Section: Epstein-barr Virus (Ebv) Is Now Firmly Associated Withsupporting
confidence: 87%
“…As previously reported (13), the L1, L2, L3, and L4 cell lines exhibited a phenotype of activated B lymphocytes with expression of CD19, CD20, CD21, CD22, CD23, and CD30 antigens, while T-cell antigens (CD3, CD4, and CD8) were not detected (data not shown). In addition, LMP-1 and EBV nuclear antigen 2 were also expressed in these lymphoblastoid cell lines known to originate from EBV-positive reservoir lymphocytes present in the original lymph nodes (13,15). The clonality of these cell lines was analyzed by PCR for immunoglobulin and T-cell-receptor ␥ chain gene rearrangements (17,19) and by Southern blot analysis of the fused terminal fragments of episomal EBV (1,9).…”
Section: Epstein-barr Virus (Ebv) Is Now Firmly Associated Withsupporting
confidence: 87%
See 2 more Smart Citations
“…10 It was also reported that EBVpositive tumors arising after the engraftment of lymph nodes from patients with Hodgkin lymphoma were derived from bystanderquiescent EBV-positive B lymphocytes and not from the EBVpositive Reed-Sternberg cells. 34 In immunocompromised patients, such as those with HIV infections and organ transplantations, EBV plays a carcinogenic role in the development of NHL, including DLBL, Burkitt lymphoma, extranodal NK/T-cell lymphoma of the nasal type, and nasopharyngeal cancer. 5 Indeed, the most frequent histological type of posttransplant lymphoproliferative disease is EBV 1 -DLBL.…”
Section: Discussionmentioning
confidence: 99%